Gene expression of estrogen receptor-alpha in orbital fibroblasts in Graves’ ophthalmopathy - Cury, Sarah Santiloni [UNESP]; Oliveira, Miriane [UNESP]; Síbio, Maria Teresa [UNESP]; Clara, Sueli [UNESP]; Luvizotto, Renata De Azevedo Melo [UNESP]; Conde, Sandro [UNESP]; Jorge, Edson Nacib [UNESP]; Nunes, Vania Dos Santos [UNESP]; Nogueira, Célia Regina [UNESP]; Mazeto, Gláucia Maria Ferreira Da Silva [UNESP] (Sociedade Brasileira de Endocrinologia e Metabologia, 2015)
Graves’ ophthalmopathy (GO) is one of the most severe clinical manifestations of Graves’ disease (GD), and its treatment might involve high-dose glucocorticoid therapy. The higher incidence of GO among females, and the reported association between polymorphisms of estrogen receptor (ER) and GD susceptibility have led us to question the role of estrogen and its receptor in GO pathogenesis. We, thus, assessed estrogen receptor-alpha (ERA) gene expression in cultures of orbital fibroblasts from a patient with GO before (controls) and after treatment with 10 nM and 100 nM dexamethasone (DEX). Orbital fibroblasts showed ERA gene expression. In the cells treated with 10 nM and 100 nM DEX, ERA gene expression was, respectively, 85% higher and 74% lower, than in the control group. We concluded that ERA gene expression is found in the orbital fibroblasts of patient with GO, which may be affected by glucocorticoids in a dose-related manner. Arch Endocrinol Metab. 2015;59(3):273-6